2018
DOI: 10.2217/cnc-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Potential for the development of light therapies in mild traumatic brain injury

Abstract: Light affects almost all aspects of human physiological functioning, including circadian rhythms, sleep–wake regulation, alertness, cognition and mood. We review the existing relevant literature on the effects of various wavelengths of light on these major domains, particularly as they pertain to recovery from mild traumatic brain injuries. Evidence suggests that light, particularly in the blue wavelengths, has powerful alerting, cognitive and circadian phase shifting properties that could be useful for treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 198 publications
0
7
0
Order By: Relevance
“…More recent work has identified a role for light in improving depression, with animal models pointing to mechanisms related to direct neuronal projections from non-vision-forming pathways to limbic regions of the brain [ 30 , 31 , 68 , 69 ]. Few studies have found morning bight light therapy effects on sleep directly, although this has not been studied to the extent of the circadian and mood fields [ 32 , 70 ]. Some possibilities include light may have direct effects on brain regions involved in sleep (e.g., direct inhibition of the ventrolateral preoptic area), or maintenance of alertness, through the same melanopsin-dependent, non-image forming pathways as circadian rhythms and mood [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recent work has identified a role for light in improving depression, with animal models pointing to mechanisms related to direct neuronal projections from non-vision-forming pathways to limbic regions of the brain [ 30 , 31 , 68 , 69 ]. Few studies have found morning bight light therapy effects on sleep directly, although this has not been studied to the extent of the circadian and mood fields [ 32 , 70 ]. Some possibilities include light may have direct effects on brain regions involved in sleep (e.g., direct inhibition of the ventrolateral preoptic area), or maintenance of alertness, through the same melanopsin-dependent, non-image forming pathways as circadian rhythms and mood [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, precisely timed BLT has been proposed as one possible, safe, and non-pharmacological way of improving sleep and post-concussive symptoms among individuals with a TBI. 18 , 21 Prior work has shown that BLT appears to be effective at improving mood and reducing fatigue and daytime sleepiness, 18 , 22 and at changing white-matter compactness within specific areas. 23 Our recent work suggests that morning BLT may also have wide ranging effects including altered circadian timing of sleep, as well as changes in thalamic volume, functional connectivity, and white matter structural connectivity, which are in turn, correlated with improvements in cognitive abilities among those with mTBI.…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythm is regulated primarily in the suprachiasmatic nucleus (SCN) of the anterior hypothalamus and can affect sleep, wakefulness, and all physiologic functions that vary across the day, including melatonin secretion [ 45 ]. TBI-induced circadian disruption may be caused by many brain functions, e.g., circadian hormone regulation and neurotransmitter functions [ 46 ]. Neuroinflammation due to brain injury may also initiate a prolonged immune response that changes the expression of clock genes in the SCN and circadian function [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%